If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7+x=14+4x
We move all terms to the left:
-7+x-(14+4x)=0
We add all the numbers together, and all the variables
x-(4x+14)-7=0
We get rid of parentheses
x-4x-14-7=0
We add all the numbers together, and all the variables
-3x-21=0
We move all terms containing x to the left, all other terms to the right
-3x=21
x=21/-3
x=-7
| 5p+6=−4p−8 | | –11x+4=–51 | | 3x-6x+2x=20 | | 6=–3r+–9 | | 7=3m+16 | | 3·(2x+5)−23=10 | | 10=x-4/3 | | 7x+10=22+3x | | (x-15)°+(2x+35)°+(2x+10)°=180° | | -3h+4=58 | | 4+y/5=-16 | | 9=18x+(-9) | | 1/9y=1 | | 93=13x | | −5/7=y−2 | | -3(10+6n)=18+6n | | 23=5y-7 | | 3x+5;x=-3 | | Y=175-15x= | | -n+8+4n=16 | | 7*x-9=4*x | | 27x-30=17x+20 | | 3/4x+3=-2x-8 | | 4(5x+6)-3(6+7x)=12 | | 2=s÷5 | | x/5+x/3=2x/8 | | Y=275-15x | | |2y–3|=25 | | -7(32u+56)=-56(-6u-43) | | x-11=4+6*x | | 5x-10=3(x+4) | | -1+2x+3x=-4+7x |